Hubungan Kreativitas Mengajar Guru dan Minat Belajar Siswa - Anita Amelia Ole; Trinancy D. Makausi (Departement of Mathematics Education, 2022)
Teaching creativity is one of the efforts made by teachers when providing learning material to their students. Creativity is said to be the ability to create a new product, which is new or which is a modification or a change by developing things that have existed before (Monawati and Fauzi, 2018). The purpose of this research is to find out the relationship between creative teaching teachers and student learning interests. The method used in this study is the Pearson moment correlation method to see the relationship between the variables studied. The questionnaire was used to obtain data for 67 students from two classes, namely class IXA and IXB, SMP (X) 01 Tikala Manado, who had filled out the questionnaire. The method used was convenience sampling to collect data in this study. The results of this study indicate that the level of teacher's teaching creativity is at a moderate level and the level of interest in student learning is at a moderate level as well. The results of this study also stated that there was a significant relationship between teacher-teaching creativity and student learning interest.